ELLIPSIS IN ERNEST HEMINGWAY’S SHORT STORY HILLS LIKE WHITE ELEPHANTS - Salih, Khelan Mohammed (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Ellipsis is a unique linguistic technique that plays a significant role in maintaining continuity in text. It is often used to avoid unnecessary repetition and achieve a consistent style, as long as the readers or listeners understand the omissions. Ellipsis typically refers to the deliberate omission of a word, sentence, or clause from a document because the omitted elements have already been mentioned and do not need to be repeated. While all languages have elliptical forms, this research focuses on the frequency of nominal, verbal, and clausal ellipsis in the English language. This article examines the use of ellipsis in Ernest Hemingway's short story Hills Like White Elephants. The aim is to demonstrate the variety and ambiguity of ellipsis in prose through vocabulary analysis. The paper follows Halliday and Hasan's functional theoretical grammar approach. The results reveal that the title of the short story itself is elliptical. The analysis also discovers that Hemingway's short story contains numerous instances of ellipsis across nominal, verbal, and clausal dimensions.